Hợp đồng lao động - chế định cơ bản của Luật lao động Việt Nam - Thu, Lê Thị Hoài (VNU Journal of Science: Social Sciences and Humanities; Vol 15 No 1, 1999)
Previously, in a long period of the old mechanism of labour management, when there was not the distinction between administrative field and labouring one, between State officials and labourers working for daily wages, the juridical foundation making arisen labouring relation is the labourers’ recruitment for regular staff according to the Decision No. 24/CP issued 13/3/1963. In the actual market economy, the juridical form making mainly arisen the relation on labouring law is the undertaking - labouring contract. The labouring contract is the most important regulation of the working law, which is a content impossible to lack in almost of all woi king laws of the countries having market economy. At a certain level, and on a certain meaning, one should speak: labouring contract is the skeleton of the working law